Reimagining Public Administration: A Participatory Model for Strengthening Community Engagement in Local Governance - Amal, Ichwakul Nur Icklasul (Universitas Pahlawan Tuanku Tambusai, 2025)
Local governance systems worldwide are increasingly adopting participatory approaches, yet many continue to fall short of enabling meaningful community engagement. This study addresses the gap between normative ideals and actual practice by reimagining a participatory model of public administration that strengthens citizen involvement in local governance. Employing a qualitative case study approach, research was conducted in two municipalities with differing participatory experiences over a six-month period through in-depth interviews, focus group discussions, participatory observation, and document analysis. The findings reveal that while formal mechanisms for participation exist, their effectiveness depends heavily on institutional design, leadership openness, the presence of intermediary actors, and the integration of informal community practices. In contrast to tokenistic participation, successful models foster trust, co-creation, and shared accountability. This study concludes that participatory governance must move beyond procedural inclusion to become embedded in administrative culture and adaptive institutional systems. The research contributes a context-sensitive, actionable model for public administrators and policymakers seeking to institutionalize participatory governance in a transformative, inclusive manner.